Social Media Impact on Women's and Children's Rights in Armed Conflicts: Legal Assertions by Third States? - Mellisa Towadi; Ana Čović; Mutia Cherawaty Thalib; Lisnawaty W Badu; Noval Sufriyanto Talani (Universitas Negeri Semarang, 2024)
This article explores how third countries can claim social media information from their citizens as a legal measure to protect and fight for the rights of women and children in armed conflict. The exploration is conducted normatively with a socio-juridical approach and a comparison of state implementation of the law. Implementing law in this approach will involve comprehensive analyses that include understanding legal texts, examining social impacts, and comparing practices across different jurisdictions to draw appropriate conclusions. This research shows that social media can serve as a platform to raise global awareness of human rights violations, provide digital evidence that can be used in international tribunals, and exert diplomatic pressure on states involved in violations. Social media also enables cross-border collaboration between governments, international organisations and NGOs to coordinate legal and advocacy efforts. However, challenges include disinformation, digital security risks, and technology access gaps that can hinder the effective use of social media as a legal tool. Nonetheless, with the right strategies, third countries can utilise social media to strengthen international law enforcement and support the fulfilment of the rights of women and children in conflict zones. In conclusion, despite significant challenges, third countries can claim the use of social media as an effective legal measure in their efforts to support and protect the rights of women and children in situations of armed conflict.